Experimental study of proton emission from 60-fs, 200-mJ high-repetition-rate tabletop-laser pulses interacting with solid targets - Spencer, I; Ledingham, K; McKenna, P; McCanny, T; Singhal, R; Foster, P; Neely, D; Langley, A; Divall, E; Hooker, C; Clarke, R; Norreys, P; et al. (2003)
Proton emission from 60-fs, 200-mJ high-repetition-rate tabletop-laser pulses interacting with solid targets was studied. A maximum proton energy of 1.5 MeV was measured for Mylar targets of thickness 20-40 μm. Results showed a maximum energy of 950 keV for 12μm for aluminum targets, and 850 keV for 12.5μm for copper targets.